Proceedings of 3rd IEEE International Conference on Image Processing
DOI: 10.1109/icip.1996.559494
|View full text |Cite
|
Sign up to set email alerts
|

Shifted fovea multiresolution geometries

Abstract: This paper describes reconfigurable geometries for image sensors based on a concentric Cartesian multiresolution lattice modified by four configuration parameters. They allow, without moving the image sensor, to examine any region of the Field of View with the highest available resolution, as well as to select the acuity profile for the regions sorrounding the fovea. The efficient processing of the multiresolution images obtained requires discrete shifts of fovea and rings whose magnitudes are calculated. Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Results obtained with both algorithms are similar, but the level sequential one is faster than the iterative (Arrebola, 1998;Bandera, 1994). These types of algorithms have been adapted to process exponential Cartesian topologies with reconfigurable structures for shifted and adaptive fovea Camacho et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained with both algorithms are similar, but the level sequential one is faster than the iterative (Arrebola, 1998;Bandera, 1994). These types of algorithms have been adapted to process exponential Cartesian topologies with reconfigurable structures for shifted and adaptive fovea Camacho et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative techniques at the optics level were also proposed (Kathman and Johnson, 1992). Based on the selective data reduction achieved with the imager, our approach is oriented to applications requiring fast processing of stereo images, using hierarchical data structures, corresponding to retinotopologies with adaptive characteristics (Camacho et al, 1996(Camacho et al, , 1997, to emulate retinae found in nature with more than one fovea, and to profit the many algorithms developed for rectangular images, unsuitable for non-Cartesian images or requiring complex transformations to adapt them. The algorithms and techniques used at the systems level are beyond the scope of the article.…”
Section: Introductionmentioning
confidence: 99%
“…According to the sampling theorem, the highest frequency that can be represented without aliasing by the display, or the display Nyquist frequency, is half of the display resolution cycles degree (6) Combining (3) and (6), we obtain the cutoff frequency for a given location by…”
Section: A Foveation Resolution and Error Sensitivity Modelsmentioning
confidence: 99%
“…A very commonly used approach is the logmap [3] superpixel method. In [3]- [6], local pixel groups are averaged and mapped into superpixels, whose sizes are determined by the retinal sampling density. In [7], a multistage superpixel approach is introduced, where a progressive transmission scheme is implemented by using variable sizes of superpixels in each stage.…”
Section: Introductionmentioning
confidence: 99%